Effectiveness of health communication programme on knowledge regarding prevention of congenital anomalies among parents: a pre-experimental study - Kumawat, Harish K.; Kharadi, Suresh; Narayan, Dev; Gaur, Rakhi; Paliwal, Chetna (International Journal of Research in Medical Sciences, 2021)
Background: Most commonly severe congenital anomalies (CA) are heart defects, neural tube defects, and Down syndrome where some CA can be prevented. The present study was aimed to improve the knowledge regarding the prevention of CA using a health communication programme (HCP) among parents in selected community area at Udaipur. Methods: Evaluative research approach and pre-experimental, one-group pre-test - post-test research designs were adopted for this study. Using a non-probability, convenient sampling technique, sixty parents were recruited from the selected community area at Udaipur city. Tools include demographic data and a self-structured knowledge questionnaire. Data were analyzed using descriptive and inferential values by IBM statistical package for social sciences (SPSS; version 23) software. Results: Data revealed that there is a lack of knowledge regarding the prevention of CA among parents and this knowledge can be increased by administering HCP on prevention of CA. The mean and standard deviation of post-test knowledge score 23.63±10.5 was higher than the mean and standard deviation of pre-test knowledge score 9.97±13.1. Conclusions: It is required to focus on HCP to improve the knowledge regarding the prevention of CA among parents in the community.